Poverty and Social Impact Analysis of Reform : Lessons and Examples from Implementation - Coudouel, Aline (Washington, DC: World Bank, 2012)
Poverty and Social Impact Analysis (PSIA) is an approach used increasingly by governments, civil society organizations, the World Bank, and other development partners to examine the distributional impacts of policy reforms on the well-being of different stakeholders groups, particularly the poor and vulnerable. PSIA has an important role in the elaboration and implementation of poverty reduction strategies in developing countries because it promotes evidence-based policy choices and fosters debate on policy reform options. This publication presents a collection of case studies that illustrate the spectrum of sectors and policy reforms to which PSIA can be applied; it also elaborates on the broad range of analytical tools and techniques that can be used for PSIA. The case studies provide examples of the impact that PSIA can have on the design of policy reforms and draw operational lessons for PSIA implementation. The case studies deal largely with policy reforms in a single sector, such as agriculture (crop marketing boards in Malawi and Tanzania and cotton privatization in Tajikistan); energy (mining sector in Romania and oil subsidies in Ghana); utilities (power sector reform in Ghana, Rwanda, and transition economies, and water sector reform in Albania); social sectors (education reform in Mozambique and social welfare reform in Sri Lanka); taxation reform (Nicaragua); as well as macroeconomic modeling (Burkina Faso).